Topographic correction of HiRISE and CaSSIS images: Validation and application to color observations of Martian albedo features. (June 2021) - Munaretto, G.; Pajola, M.; Lucchetti, A.; Re, C.; Cremonese, G.; Simioni, E.; Cambianica, P.; Thomas, N.
Abstract: The topographic correction of satellite images has to be applied to both disentangle albedo features from illumination effects induced by local topography and perform spectrophotometric analyses of planetary surfaces. This work focuses on the modeling and removal of surface brightness variations induced by topography, referred as topographic shading, from high resolution images of Mars. Topographic shading can be modeled through functions of the surface illumination and observation angles called disk functions. We consider four disk functions that are widely used in planetary photometry: the Lambert, Lommel-Seeliger, Akimov and Minnaert disk functions. We test and evaluate their performances in removing topographic shading from High Resolution Imaging Science Experiment (HiRISE) and Colour and Surface Science Imaging System (CaSSIS) images. We here validate our method, moreover, we report scientific applications to single or multi-band datasets by analyzing topographically corrected HiRISE colour observations of Martian recurring slope lineae and dust devil tracks, as well as CaSSIS panchromatic observations. Highlights: We present a methodology to apply the topographic correction to planetary images. We apply our method to correct HiRISE and CaSSIS images from topographic shading. We validate our method with published photometry of Martian Recurring Slope Lineae. The corrected images allow to study the photometry of Martian albedo features. Multi-band photometry of Recurring Slope Lineae hints towards a dry-dust origin.